Conforming to partnership values: a qualitative case study of public–private mix for TB control in Ghana - Joshua Amo-Adjei (Global Health Action, 2016)
Background: Public–private mix (PPM) can supplement public sector initiatives, including public health. As National Tuberculosis Control Programmes around the world embrace PPM, conforming to the four key principles of partnership values of beneficence, non-maleficence, autonomy, and equity as espoused by the World Health Organization can provide a useful framework to guide successful implementation. Design: This is a qualitative case study of PPM in tuberculosis (TB) control, which utilised a purposive sample of 30 key stakeholders involved in TB control in Ghana. Respondents comprised an equal number of respondents from both the public and private sectors. Semi-structured in-depth interviews (IDI) were conducted with respondents. Data emanating from the IDIs were analysed deductively. Results: Although the respondents’ perceptions about beneficence were unanimous, their views about non-maleficence, autonomy, and equity appeared incongruous with the underlying meanings of the PPM values. Underlying the unfavourable perceptions were disruptions in funding, project implementers’ failure to follow-up on promised incentives, and private providers lost interest. This was perceived to have negatively affected the smooth implementation of PPM in the country. Conclusions: Going forward, it is imperative that future partnerships are built around utilitarian principles and also adhere to the dictates of agreements, whether they are ‘soft’ or standard contracts.